รีเทนชันแฟคเตอร์และประสิทธิภาพของการแยกสารประกอบประเภทอนุกรมโฮโมโลกัสในไมโครอิมัลชันอิเล็กโทรไคเนทิกโครมาโทกราฟี : รายงานผลการวิจัย - ธรรมนูญ หนูจักร (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Retention factor (k), retention index (I) and efficiency (N) for homologous series compounds, such as alkylbenzenes (BZ), alkylaryl ketones (PN), alkylbenzoates (BA) and alkylparabens (PB), in microemulsion electrokinetic chromatography (MEEKC) with suppressed electroosmosis were investigated in a wide range of the concentration of sodium dodecyl sulphate ([SDS]), separation temperature and applied voltage. An MEEKC buffer used contained a phosphate buffer at pH 2.5, 1.0% v/v n-octane as oil, 100 to 200 mM SDS as surfactant and 890 mM 1-butanol as co-surfactant. Retention index is independent of [SDS], temperature and applied voltage, while k linearly increases with increasing [SDS], but linearly decreases with increasing temperature and applied voltage. The efficiency increases with increasing [SDS], while decreases with higher temperature and applied voltage. At given [SDS], temperature and applied voltage, the values of N are insignificantly different for each homologous series, while different for different homologous series. Over a wide range of [SDS], temperature and applied voltage, the linear relationship between log k and number of carbons (z) is obtained. The equation of log k as a function of z and [SDS] was modified to predict the values of log k of homologous series compounds. At given [SDS], excellent agreement was found between observed and predicted values of log k analytes in MEEKC. Using BZ as standards, the linear calibration plots between log K[subscript ow] versus log k or log K[subscript ow] versus I were obtained over a wide range of [SDS], and the values of log K[subscript ow] for PN, BA and PB were predicted from log k and I, where log K[subscript ow] is the logarithm of octanol-water distribution constant. Using paired t-test analysis at 95% confidence interval of the mean, non significant difference was found for the predicted values of log K[subscript ow] obtained from log k and I. In addition, good agreement was also found for the predicted and literature values of log K[subscript ow] for each analyte.